Scarecrow's Secret - Amery, Heather; Illustrated by Cartwright, Stephen (London Usborne, 2015)
The scarecrow on Apple Tree Farm is very good at his job. Nobody knows why, until one day Sam and Poppy discover his secret... A charming story from the Farmyard Tales series for beginner readers, with simple text, beautiful illustrations by Stephen Cartwright and four fun puzzles for children to solve at the end of the story.
Include Illustrations
Keywords: Scarecrows -- Farms -- Vocabulary